2022
DOI: 10.1101/2022.03.07.483218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physiologically Based Multiphysics Pharmacokinetic Model for Determining the Temporal Biodistribution of Targeted Nanoparticles

Abstract: Nanoparticles (NP) are being increasingly explored as vehicles for targeted drug delivery because they can overcome free therapeutic limitations by drug encapsulation, thereby increasing solubility and transport across cell membranes. However, a translational gap exists from animal to human studies resulting in only several NP having FDA approval. Because of this, researchers have begun to turn toward physiologically based pharmacokinetic (PBPK) models to guide in vivo NP experimentation. However, typical PBPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the case of PBPK models and related PBPK analyses, intermediate to advanced programming skills are required, which present a considerable disadvantage for its widespread use in the field [ 69 ]. MATLAB provides a range of mathematical and numerical methods for solving PBPK model equations, parameter estimation, and sensitivity analysis [ 53 , 54 , 55 , 56 , 61 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. In particular, several MATLAB toolkits can be used for modeling, simulating, and analyzing PBPK systems, namely SimBiology [ 57 , 77 , 78 , 79 , 80 ], PottersWheel [ 81 , 82 ], and IntiQuan IQM Tools [ 70 ].…”
Section: Main Pbpk Modeling Softwarementioning
confidence: 99%
See 2 more Smart Citations
“…In the case of PBPK models and related PBPK analyses, intermediate to advanced programming skills are required, which present a considerable disadvantage for its widespread use in the field [ 69 ]. MATLAB provides a range of mathematical and numerical methods for solving PBPK model equations, parameter estimation, and sensitivity analysis [ 53 , 54 , 55 , 56 , 61 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. In particular, several MATLAB toolkits can be used for modeling, simulating, and analyzing PBPK systems, namely SimBiology [ 57 , 77 , 78 , 79 , 80 ], PottersWheel [ 81 , 82 ], and IntiQuan IQM Tools [ 70 ].…”
Section: Main Pbpk Modeling Softwarementioning
confidence: 99%
“…Julia [ 128 ] is a flexible dynamic programming language appropriate for scientific and numerical computing. It has been shown that in the context of PBPK models, a DifferentialEquations.jl package outperforms MATLAB in solving a stiff system of ordinary differential equations [ 72 ].…”
Section: Auxiliary Pbpk Modeling Softwarementioning
confidence: 99%
See 1 more Smart Citation